Enzo Gradassi interviews Antonio Ferrini: Descriptive Translation Study onRegional Oral Italian Transcribed - Anguita Martinez, Victor (2025)
Diatopic and diastratic variation dominate Italy’s linguistic reality. In this crossroads of regional varieties and registers is placed the italiano dei semicolti, a low register Italian characteristic of non-instructed people whose capacity for abstraction in oral contexts are reduced. In Manicomio 1914 (Conti, 1978), published by Mazzota Editore, the epistolary biography of Adalgisa Conti is included, written during her stay in the Arezzo mental hospital, an interview with Antonio Ferrini, former mayor of Anghiari (a small Tuscan town), is collected. In the dialogue between the interviewer and the interviewee, the semi-educated Italian emerges and the conversation that has been faithfully transcribed for the publication of the work predominates. In this descriptive Translation study, we will define the characteristics that define this linguistic phenomenon to later focus on the translation issues intrinsic to these variational factors that condition the translation process so to not rewriting the work in L2 with a register normative that reduces the diversity of the original.